Livros, leituras e leitores: a literatura do Espírito Santo no vestibular da UFES - Tragino, Arnon (2015)
The paper is concerned with analyzing the presence of the Literature of Espírito Santo, which was inserted in Federal University of Espírito Santo’s Selection Process (college entrance) from 2005 to 2014. Therefore, the focus of analysis was: a) on the official announcement of selection processes, where it is presented content and the form of assessment; b) on the lists of books and texts for required reading of literary themes, which compose the body of specific issues to be addressed in exams; c) on the objective questions, discursive questions, and wording tests, which connect to the literature mentioned previously; d) the expected responses proposed by board of examiners in discursive questions. The theoretical and critical supports chosen were the considerations of Wolfgang Iser, the Aesthetics of Reception, to understand literature and the prospect of reader proposed by these documents, and the Cultural History as proposed by Roger Chartier, in order to reflect upon what notion of book and reading the exam indicates. Furthermore, we also approach the course the entrance exams to higher education made in Brazil and in the State of Espírito Santo, connecting it to the literary history and formation of literature readers formed by schooling processes.